2015
DOI: 10.1186/s12889-015-1604-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a physically more active lifestyle based on one’s own values: the results of a randomized controlled trial among physically inactive adults

Abstract: BackgroundThe high prevalence of physical inactivity has led to a search for novel and feasible interventions that will enhance physical activity, especially among the least physically active individuals. This randomized controlled trial aimed to determine the effectiveness of a value-based intervention to promote a physically more active lifestyle among physically inactive adults. The framework of the study was based on Acceptance and Commitment Therapy (ACT).MethodsPhysically inactive participants aged 30 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 63 publications
2
47
1
Order By: Relevance
“…Indeed, a previous study demonstrated that physically active adults demonstrated better mindfulness skills (a component of PF) in comparison to less physically active adults (Kangasniemi et al 2014). Contrary to some literature (Kangasniemi et al 2014, Kangasniemi et al 2015, we observed a non-significant association between PF and PA measures, indicating that individuals with or without greater PF engage in similar levels of PA. In support of our findings, a recent study (Mutikainen et al 2015) also reported no association between PF and PA levels, suggesting that future research should use an exercise-specific AAQ version in place of the generic AAQ-II questionnaire (Forman et al 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Indeed, a previous study demonstrated that physically active adults demonstrated better mindfulness skills (a component of PF) in comparison to less physically active adults (Kangasniemi et al 2014). Contrary to some literature (Kangasniemi et al 2014, Kangasniemi et al 2015, we observed a non-significant association between PF and PA measures, indicating that individuals with or without greater PF engage in similar levels of PA. In support of our findings, a recent study (Mutikainen et al 2015) also reported no association between PF and PA levels, suggesting that future research should use an exercise-specific AAQ version in place of the generic AAQ-II questionnaire (Forman et al 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…In regard to PA, PF has been considered an aversive cognitive situation that can be associated with physical inactivity (Kangasniemi et al 2014). Interventions which target improving one's PF, such as acceptance and commitment therapy, have achieved positive health behaviours including increasing PA among physically inactive adults and reducing weight in obese individuals (Kangasniemi et al 2015, Lillis et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective observational study demonstrated that individuals with higher levels of dispositional mindfulness were more likely to follow through with baseline intentions to be physically active at 5 weeks follow-up [26]. A few ACT randomized controlled trials (RCTs) showed promising effects on increasing physical activity after 1 h to 6 months of follow-up time [2730]. A recent observational study showed that mindfulness was associated with physical activity levels only in participants with weak habits for regularly doing physical activity [31].…”
Section: Physical Activitymentioning
confidence: 99%
“…To date the interventions for physical activity that have included mindfulness have been based on Acceptance and Commitment Therapy [7578]. Three of the four randomized controlled trials showed significant effects on physical activity outcomes including self-report physical activity (Brief Physical Assessment Tool assessing number of physical activity bouts per week [79], International Physical Activity Questionnaire [76]) and directly assessed physical activity (pedometer-assessed step count [76] and exercise tolerance time defined as duration of loaded pedaling [77]).…”
Section: Mindfulness-based Interventions For Cardiovascular Disease Rmentioning
confidence: 99%